Effect of Activity, Massage, Job Control-Demand on Ergonomic Posture of Office Workers - Agatha, Yusly; Kartamihardja, Sobarna; Malik, Rahadian; Rahmiyati, Ayu Laili; Kosasih, Kosasih; Yuliyaty, Farida (Poltekkes Kemenkes Surakarta, 2025)
Background: Work-related musculoskeletal disorders (WMSDs) are common occupational injuries affecting muscles, joints, and the skeletal system. Effective management requires both individual and workplace support. Physical activity, therapy compliance, job control, and job demand are key factors influencing ergonomic posture and pain management outcomes. This study examined the effects of physical activity, massage therapy compliance, job control, and job demand on ergonomic posture of office workers in PT. X’s musculoskeletal pain management program. Methods: Quantitative and cross-sectional research using proportional random sampling, data from 100 office workers of PT X were analyzed with multiple linear regression (T-test and F-test) via SPSS. The ergonomic posture was evaluated through Rapid Assessment Office Strain (ROSA). Results: All variables significantly affected ergonomic posture (F = 227.621, p < 0.001). Massage therapy compliance contributed the most (40.2%), followed by physical activity (33.1%), job demand (9.2%), and job control (8.1%). Conclusion: Physical activity and therapy compliance had the strongest positive effects on ergonomic attitudes, emphasizing their role in improving musculoskeletal pain management at PT. X. It is recommended that workplace programmes prioritise efforts to increase physical activity and therapy compliance, as these two factors have the strongest positive influence on ergonomic attitudes and musculoskeletal pain management.